Early Retirement and Inequality in Britain and Germany: How Important Is Health? - Jennifer Roberts; Nigel Rice; Andrew M. Jones (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
Both health and income inequalities have been shown to be much greater in Britain than in Germany. One of the main reasons seems to be the difference in the relative position of the retired, who, in Britain, are much more concentrated in the lower income groups. Inequality analysis reveals that while the distribution of health shocks is more concentrated among those on low incomes in Britain, early retirement is more concentrated among those on high incomes. In contrast, in Germany, both health shocks and early retirement are more concentrated among those with low incomes. We use comparable longitudinal data sets from Britain and Germany to estimate hazard models of the effect of health on early retirement. The hazard models show that health is a key determinant of the retirement hazard for both men and women in Britain and Germany. The size of the health effect appears large compared to the other variables. Designing financial incentives to encourage people to work for longer may not be sufficient as a policy tool if people are leaving the labour market involuntarily due to health problems.
Keywords: J26; I10; C23; C41; 330; health; early retirement; hazard models